2005
DOI: 10.2175/193864705783869880
|View full text |Cite
|
Sign up to set email alerts
|

A Large-Scale Uv Pilot-Plant Study: Tertiary Effluent Disinfection and Effect on Ndma and Cyanide

Abstract: The Sanitation Districts of Los Angeles County (Sanitation Districts) are currently facing new regulatory issues related to NDMA and cyanide. To prevent NDMA formation from chloramination, the Sanitation Districts are considering the use of ultraviolet (UV) disinfection to replace chloramination. UV disinfection may also result in incidental removal of NDMA. However, a recent study indicated that low levels of cyanide might be formed as a result of UV irradiation. To fully evaluate the effect of UV on tertiary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The major products of the reaction are DMA and nitrite, while minor products include nitrate, formaldehyde, formate, and perhaps methylamine. Because UV photolysis may not destroy NDMA precursors [12], some have suggested that reformation of NDMA may occur within drinking water distribution systems if chlorination is performed after the UV treatment [13] And UV treatmen for NDMA will be feasible but more expensive [14 ].…”
Section: Methods Of Dma Removalmentioning
confidence: 99%
“…The major products of the reaction are DMA and nitrite, while minor products include nitrate, formaldehyde, formate, and perhaps methylamine. Because UV photolysis may not destroy NDMA precursors [12], some have suggested that reformation of NDMA may occur within drinking water distribution systems if chlorination is performed after the UV treatment [13] And UV treatmen for NDMA will be feasible but more expensive [14 ].…”
Section: Methods Of Dma Removalmentioning
confidence: 99%